Histology of the mucosa of the oesophagogastric junction and the stomach in adult Rana perezi. - Gallego-Huidobro, J (1996)
The histological structure of the frog digestive mucosa changes at the oesophagogastric junction. The pseudostratified ciliated mucosal epithelium of oesophageal type changes to a simple mucus-secreting epithelium of gastric type. The glands straighten and the muscularis mucosae develops as a complete layer. The muscularis increases in thickness. Unlike the mammalian stomach, in the frog the surface of the plicae forms convoluted ridges that delimit furrow-shaped pits. Two types of gastric glands are distinguished, fundal and pyloric. The former consist of mucous, oxynticopeptic and endocrine cells. The pyloric glandular cells are mainly of mucus-secreting type with scattered endocrine cells. Scattered endocrine cells of P, D, G, A, EC, and EC-L-like types are found in the glands along the stomach. It is concluded that the mucosal structure of the anuran oesophagogastric junction and stomach is less complicated than that of mammals, including man.